Teaching Vocabulary through Computers - Slánská, Magdalena (Univerzita Pardubice, 2013)
The thesis deals with the theme learning vocabulary through computers. I begin with the term learning viewed from the perspectives of behaviourist, cognitivist and constructivist learning theories. then computer is presented as a modern learning tool able to provide learners with rich learning environment, when used with respect to the knowledge of the learning process. Positive and negative features of implementing computer technology into second language learning are discussed. at last the role of vocabulary in the second language learning is defined together with the category of young learners. With respect to the findings stated, the role of computer assisted vocabulary instruction is reflected. For the purpose of the practical part an interactive audiovisual programme was developed. the programme aims to offer a rich learning environment and to provide concrete learners with a multimedia support linked directly with the vocabulary items introduced in their course books. the programme was complemented with pre- and post- activities and the project was tested in a real school environment. observation of the learners' interaction with the programme was taken as a feedback and the project was redesigned in order to support the learners in a more suitable way.
Výuka slovní zásoby s využitím počítačů
Keywords: výuka s podporou počítače; výuka anglického jazyka; osvojování slovní zásoby; computer assisted learning; english language learning; acquiring vocabulary